2016
DOI: 10.1002/prca.201500082
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry based translational proteomics for biomarker discovery and application in colorectal cancer

Abstract: Colorectal cancer (CRC) is a leading cause of cancer-related death in the world. Clinically, early detection of the disease is the most effective approach to tackle this tough challenge. Discovery and development of reliable and effective diagnostic tools for the assessment of prognosis and prediction of response to drug therapy are urgently needed for personalized therapies and better treatment outcomes. Among many ongoing efforts in search for potential CRC biomarkers, MS-based translational proteomics provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…Indeed, Zhang et al showed that the abundance of mRNA transcripts did not efficiently predict the abundance of proteins. This observation highlights the importance of proteogenomic integration to strengthen the data in the discovery of biomarkers, or of potential therapeutic targets in colorectal cancer [29,103]. Among the proteins emerging from different studies [34,61,62,63,64,65,66,67,71,72] and observed in Zhang’s proteogenomic study [29], we note the important presence of proteins involved in the regulation of the apoptotic process and in the negative regulation of the cellular protein metabolic process (Figure 3), identifying common proteins and possible biomarkers that overlap between these studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, Zhang et al showed that the abundance of mRNA transcripts did not efficiently predict the abundance of proteins. This observation highlights the importance of proteogenomic integration to strengthen the data in the discovery of biomarkers, or of potential therapeutic targets in colorectal cancer [29,103]. Among the proteins emerging from different studies [34,61,62,63,64,65,66,67,71,72] and observed in Zhang’s proteogenomic study [29], we note the important presence of proteins involved in the regulation of the apoptotic process and in the negative regulation of the cellular protein metabolic process (Figure 3), identifying common proteins and possible biomarkers that overlap between these studies.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the discovery of a biomarker, or a signature of biomarkers, capable of predicting the response of patients with colorectal cancer to a given radiotherapy and/or chemotherapy treatment would invariably have many advantages: First of all, for the patient, in avoiding physically and psychologically demanding treatment; secondly, for physicians, in guiding their clinical decisions; and finally, for reducing health care costs (Figure 2) [34]. Unfortunately, despite numerous proteomic studies, no biomarkers identified after the discovery and/or validation steps are currently the subject of clinical studies [102,103], and this problem is very well discussed by Diamandis et al [102]. However, as shown in Table 1 and Table 2, many proteins identified in the various proteomic studies are found in Zhang’s proteogenomic study (*) [29].…”
Section: Discussionmentioning
confidence: 99%
“…MRM assay is a target MS technique based on ESI–MS [182–191]. The operating principle composes following stages: in the first quadrupole (Q1), an analyte ion with certain mass will be selected; the selected ions will be consequently fragmentized by collision‐induced dissociation (CID); a single or multiple specific fragment ions are selected again by the second quadrupole (Q2) and transmitted into the third quadrupole (Q3) for detection (Figure 5I) [192–197].…”
Section: Bioanalytical Methods For Polyethylene Glycols and Pegylatedmentioning
confidence: 99%
“…In addition, proteomics could provide biomarkers that define differences in resistance to therapy, prognosis and metastatic spread in a specific subtype. Mass spectrometry (MS)-based technologies are powerful tools for the investigation of biomarkers in clinical samples, 9 and SWATH-MS (Sequential Window Acquisition of all THeoretical Mass Spectra-MS) is an innovative MS approach that allows the quantification of almost all peptides and proteins present in a single sample being useful in large sample cohort studies. 10,11 Therefore, the aim of our study was to identify and quantify differential expression of proteins in clinical samples of CRC using the SWATH-MS approach of proteomic analysis and to establish potential subtypes of CRC based on differential expression of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, proteomics could provide biomarkers that define differences in resistance to therapy, prognosis and metastatic spread in a specific subtype. Mass spectrometry (MS)–based technologies are powerful tools for the investigation of biomarkers in clinical samples, and SWATH‐MS (Sequential Window Acquisition of all THeoretical Mass Spectra‐MS) is an innovative MS approach that allows the quantification of almost all peptides and proteins present in a single sample being useful in large sample cohort studies …”
Section: Introductionmentioning
confidence: 99%